Prevalence of Giant Cell Arteritis Relapse in Patients Treated With Glucocorticoids: A Meta‐Analysis. Issue 6 (19th May 2020) - Mainbourg, Sabine; Addario, Alexandra; Samson, Maxime; Puéchal, Xavier; François, Mathilde; Durupt, Stéphane; Gueyffier, François; Cucherat, Michel; Durieu, Isabelle; Reynaud, Quitterie; Lega, Jean‐Christophe
Abstract : Objective: The relapse rate of patients with giant cell arteritis (GCA) treated with glucocorticoids (GCs) alone varied widely in observational series and randomized controlled trials (RCTs). The purpose of this systematic review was to evaluate the prevalence of relapse and predisposing factors in patients receiving GCs alone. Methods: We searched Medline up to December 2017. The prevalence of relapse was pooled using a random‐effects model. Results: A total of 34 studies (2, 505 patients), comprising 8 RCTs, were included. The overall prevalence of relapse was 47.2% (95% confidence interval 40.0, 54.3) with a high heterogeneity (I 2 = 93%). Prevalence of relapse was significantly higher for patients included in an RCT compared to those included in an observational study ( P < 0.0001), but was not significantly different according to design ( P = 0.06). The relapse rate was associated with year of publication (34 studies, rate increase of 8.3% for 1 decade; P < 0.0001) and with shorter GC regimens (17 studies, rate decrease of 1.7% for 1 additional month; P < 0.001), the duration of scheduled GC therapy being shorter in RCTs (12.8 months) compared to observational studies (28.8 months). The effective duration of GC therapy ( P = 0.23), initial GC dose ( P = 0.49), duration of follow‐up ( P = 0.14), sex ( P = 0.29), and age ( P = 0.43) were not associated with the prevalence of relapse. Conclusion: GCA relapses occur in half of patients and without improvement across decades in patients receiving GC alone, and the relapse rate is more related to short duration of GC administration than to the initial dose at induction. These results advocate for trial design with at least 12 months of GC therapy.